MENTAL HEALTH STATUS OF BPSU STUDENTS: BASIS FOR ENHANCED MENTAL HEALTH SERVICES - Ma. Fatima B. Bacala; Rochelle G. Tiongson; Lady Fatima D. Visda; Queen M. Quiroz; Roland Paulo B. Manaligod (LPPM UNiversitas Bina Mandiri Gorontalo, 2024)
This study employed an explanatory sequential mixed method design to investigate the mental health status of students at Bataan Peninsula State University Philippines, focusing on the emotional, cognitive, social, and meaning and purpose dimensions. Additionally, an evaluation of the university's current mental health program was conducted to identify its shortcomings and potential areas for enhancement. Utilizing a standardized and validated questionnaire alongside a focused group discussion, the findings indicate that a majority of students exhibit a high level of positive mental health. Overall, students rated the performance of the Guidance and Counseling Services in implementing their Mental Health Program as satisfactory in meeting their expectations. The highest mean rating was attributed to the promotion of positive mental health, whereas the lowest was related to the effective development, coordination, and administration of the Mental Health Program. Furthermore, significant associations were found between students' profiles—such as sex, birth order, number of siblings, parent's income, and program—and their mental health status concerning the meaning and purpose dimension. Additionally, classifications based on student status, year level, and disability were significantly linked to overall mental health. These associations were consistent across all mental health areas: emotional, cognitive, social, and meaning and purpose. However, when analyzing overall mental health mean ratings by age, gender, religion, address classification, parents’ marital status, and campus, no substantial differences were observed, indicating that no significant relationships can be inferred.